PENGARUH KOMPETENSI, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. SEMEN BOSOWA MAROS - Ali Baba (EKUITAS (Jurnal Ekonomi dan Keuangan), 2014)
Influence of Competency, Communication and Cultural Organization on Employee Performance PT. Semen Bosowa Maros. To know and analyze the influence of competence, communication and organizational culture on employee performance of PT. Semen Bosowa Maros and as for the benefits to the parties bound research is expected to develop a repertoire of knowledge in the field of human resource management especially concerning competence, communication and organizational culture on employee performance. Data used in this study are primary data that responses to questionnaires from respondents with data analysis using multiple linear regression with SPSS 20. The sample in this research is 93 respondents employees of PT. Semen Bosowa Maros. Results of this study stated that based on the analysis of data in the show showed that 66.2% of an employee's performance is influenced by competence, communication and organizational culture this means that 33.8% (100% - 66.2%) the employee's performance is influenced by other factors, where the regression results indicate that the independent variable is the style of competency, communication and organizational culture positive and significant impact on the performance of employees of PT. Semen Bosowa Maros